2023
DOI: 10.3390/fermentation9040332
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Copper Oxide Nanoparticles Using Sesbania grandiflora Leaf Extract and Their Evaluation of Anti-Diabetic, Cytotoxic, Anti-Microbial, and Anti-Inflammatory Properties in an In-Vitro Approach

Abstract: Green methods of synthesizing nanoparticles are safer than chemical and physical methods, as well as being eco-friendly and cost-efficient. In this study, we use copper oxide nanoparticles (CuO NPs) fabricated with Sesbania grandiflora (Sg) (Hummingbird tree) leaves to test the effectiveness of green synthesizing methods. The attained Sg-CuO NPs physical and optical nature is characterized by UV-Vis spectroscopy Differential Reflectance Spectroscopy (UV-Vis DRS), Fourier Transform Infra-Red spectroscopy (FTIR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…More than 93% of a cell’s growth was effectively inhibited by 100 μg/mL of copper nanoparticles. Similar to this, Ramasubbu et al [ 55 ] showed that treatment of HepG2 cells with copper nanoparticles has anticancer effects.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…More than 93% of a cell’s growth was effectively inhibited by 100 μg/mL of copper nanoparticles. Similar to this, Ramasubbu et al [ 55 ] showed that treatment of HepG2 cells with copper nanoparticles has anticancer effects.…”
Section: Resultssupporting
confidence: 58%
“…The growth of E. coli was observed to be inhibited by Sg-CuO nanoparticles at doses of 100 and 125 µg, resulting in the formation of zones of inhibition with diameters measuring 10 ± 1.21 mm and 14 ± 1.39 mm, respectively. The results indicated a significant difference (17 0.46 mm) in favor of the treatment being compared to streptomycin [ 55 ]. The efficacy of copper nanoparticles derived from N. cataria as bactericidal agents.…”
Section: Resultsmentioning
confidence: 99%
“…2 A. The calculated band gap energy from the UV–visible absorption spectrum is 1.006 eV 56 , 57 . The decrease in particle size has been triggered with a shift in absorption towards smaller wavelengths.…”
Section: Resultsmentioning
confidence: 95%
“…The degree of sensitivity of microorganisms to the test samples was determined by the size of the zone of no growth of microorganisms. Microbiological studies were carried out in laminar, pre-irradiated with a UV lamp for sterilization before sowing test cultures on nutrient media [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Methodsmentioning
confidence: 99%